Survival and multiplication of Vibrio cholerae in the upper bowel of infant mice. - Baselski, V S (1978)
The survival and multiplication of Vibrio cholerae strains of varying virulence in the upper bowel of orally challenged infant mice early in infection has been examined. Analysis of changes in the apparent specific activity (counts per minute per colony-forming unit) of the cell population after 4 h compared with the inoculum indicated that strain CA401 established a viable, multiplying cell population, whereas strains VB12 (a rough variant) and 569B were subject to host bactericidal and bacteriolytic mechanisms. An analysis of parameters which may affect the specific activity is included. We have defined the infective potential of the strains in terms of the changes in specific activity. The relative infective potentials are CA401 greater than 569B greater than VB12.